The history of the formation of the psychological thought of the crimean tatar people (from prehistory to the found ation of the Crimean khanate) - Arzy Mambetova; Serhii Shykovets (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
Here is viewed and analyzed such an important part of a comprehensive process of formation and development of psychological thought in Ukraine, as the history of the formation of psychological thought of the Crimean Tatar people. Unfortunately, the subject of this theoretical research so far has been extremely poorly represented and disclosed in the context of domestic psychological, historical, political, cultural sciences and in the context of their foreign counter parts in the framework of the world science in general. Therefore this article can beconsideredas a trialinthistheme.